The Transcription Factor MYB37 Positively Regulates Photosynthetic Inhibition and Oxidative Damage in Arabidopsis Leaves Under Salt Stress - Li, Yuanyuan; Tian, Bei; Wang, Yue; Wang, Jiechen; Zhang, Hongbo; Wang, Lu; Sun, Guangyu; Yu, Yongtao; Zhang, Huihui (Frontiers in Plant Science, 2022)
MYB transcription factors (TFs) mediate plant responses and defenses to biotic and abiotic stresses. The effects of overexpression of MYB37, an R2R3 MYB subgroup 14 transcription factors in Arabidopsis thaliana, on chlorophyll content, chlorophyll fluorescence parameters, reactive oxygen species (ROS) metabolism, and the contents of osmotic regulatory substances were studied under 100 mM NaCl stress. Compared with the wild type (Col-0), MYB37 overexpression significantly alleviated the salt stress symptoms in A. thaliana plants. Chlorophyll a (Chl a) and chlorophyll b (Chl b) contents were significantly decreased in OE-1 and OE-2 than in Col-0. Particularly, the Chl a/b ratio was also higher in OE-1 and OE-2 than in Col-0 under NaCl stress. However, MYB37 overexpression alleviated the degradation of chlorophyll, especially Chl a. Salt stress inhibited the activities of PSII and PSI in Arabidopsis leaves, but did not affect the activity of PSII electron donor side oxygen-evolving complex (OEC). MYB37 overexpression increased photosynthesis in Arabidopsis by increasing PSII and PSI activities. MYB37 overexpression also promoted the transfer of electrons from QA to QB on the PSII receptor side of Arabidopsis under NaCl stress. Additionally, MYB37 overexpression increased Y(II) and Y(NPQ) of Arabidopsis under NaCl stress and decreased Y(NO). These results indicate that MYB37 overexpression increases PSII activity and regulates the proportion of energy dissipation in Arabidopsis leaves under NaCl stress, thus decreasing the proportion of inactivated reaction centers. Salt stress causes excess electrons and energy in the photosynthetic electron transport chain of Arabidopsis leaves, resulting in the release of reactive oxygen species (ROS), such as superoxide anion and hydrogen peroxide, leading to oxidative damage. Nevertheless, MYB37 overexpression reduced accumulation of malondialdehyde in Arabidopsis leaves under NaCl stress and alleviated the degree of membrane lipid peroxidation caused by ROS. Salt stress also enhanced the accumulation of soluble sugar (SS) and proline (Pro) in Arabidopsis leaves, thus reducing salt stress damage to plants. Salt stress also degraded soluble protein (SP). Furthermore, the accumulation of osmoregulation substances SS and Pro in OE-1 and OE-2 was not different from that in Col-0 since MYB37 overexpression in Arabidopsis OE-1, and OE-2 did not significantly affect plants under NaCl stress. However, SP content was significantly higher in OE-1 and OE-2 than in Col-0. These results indicate that MYB37 overexpression can alleviate the degradation of Arabidopsis proteins under NaCl stress, promote plant growth and improve salt tolerance.